Pemberdayaan Usaha Mikro, Kecil Dan Menengah (UMKM) Di Desa Gempol Melalui Kegiatan Pasar Sawang - Fauziyyah, Rima (LPPM Universitas Insan Pembangunan, 2024)
Gempol Village is one of the villages located in the southernmost area of Rejoso Sub-district, Nganjuk Regency. Most of the people in this area work as farmers, but some people also have UMKM which are an additional source of income for them. One of the obstacles that hampers these UMKM is the lack of facilities and empowerment carried out by the village government. The research methods used are observation and literature study. According to the results of observations, empowering UMKM that can be done is to make market access wider by creating a